Post-war medical policy (report) - Daily Herald ; Scottish Union of Bakers, Confectioners and Bakery Workers
1941-10-29 1941 1940s 6 pages the Minister's statement that the official policy now pronounced is that individuals can obtain appropriate treatment for any case but at a price. That price will no doubt vary according to the means of the patient. This implies, (i) a Means Test through the Hospitals Almoners' System and (ii) treatment discrimination purely on grounds of wealth, or ability to pay. It is important to bear in mind that already many of these hospitals not only have contributory schemes which are practically without proper national co-ordination, making contributions to the scattered hospitals for whom even the British Hospitals Association cannot be regarded as the authoritative spokesman, but have paying wards attached. Is it to be understood that ratepayers' or taxpayers' contributions are to be made to such hospitals which already have paying wards attached? The place too of the municipal hospitals which have made marvellous strides in the last 10 years, since they have been freed from the incubus of the Poor Law, may be hindered in their development, equipment, and excellent specialist staffing, as a result of this policy. The voluntary hospitals, especially the teaching centres may claim all the best cases for the purposes of the tuition of students, relegating the chronic cases to the municipal hospitals. This policy too will also result in a further demand for the payment of the medical staff in voluntary hospitals who now receive their remuneration indirectly from a contact with the future doctors of Great Britain. This premature decisive announcement has taken the sails out of the enquiry by the Beveridge Committee into Social Services on which reliance was being placed. It is an attempt to stake out a claim for the vested interests for the voluntary hospitals, and separates the medical services from the social services. It is a deplorable policy cutting across completely in my view the policy of the Trade Union Movement with regard to voluntary hospitals and medical services generally, and it especially jettison the principle that free treatment should be available on equal term to every citizen irrespective of their means. HBM/EM/111/29.10.41. 292/842/2/122